ETOS KERJA PEMIMPIN USAHA JASA TRANSPORTASI (STUDI KASUS DI TERMINAL BANDAR RAYA PAYUNG SEKAKI ) - Khairul Amali; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The purpose of this research is to know work ethos of transportation service entrepreneurs, economic behavior of transportation service entrepreneurs, and factors influencing work ethic of transportation service employers. Working ethos is according to Sukriyanto (2000) is a morale that is owned by the community to be able to work better in order to obtain the value of their lives. Someone who has a good work ethic will certainly enjoy the process of their work without much complaints so that the results obtained from his job feels more satisfying. This research was conducted at terminal of Bandar Raya Payung Sekaki Pekanbaru City. The population of this research is all transportation service business leaders, while the sample in this research is the leader of the awarded transportation service business. There are several elements of analysis in this study, the first work ethic that includes morale, future orientation, discipline, responsibility, diligence, and healthy competition. Second, economic behavior that is seen from saving, saving, and time management. Third, factors affecting work ethos are Religion, culture, social politics, environmental or geographical conditions, educational background, economic structure, and intrinsic motivation of individuals. This research technique is qualitative is a research procedure that produce descriptive data in the form of writing and behavior that can be observed from the subject itself. Based on research in the field found that the leader of the transportation service business is considered to have a high work ethic and good economic behavior, then the most dominant factors affect the work ethic of transportation service business leaders is the religion, culture and intrinsic motivation of individuals, while the no effect is the social factor political.Keywords: Ethos, Work, Entrepreneur